Design of a MEMS bionic vector hydrophone with piezo-gated MOSFET readout. (April 2020) - Amiri, Peyman; Kordrostami, Zoheir; Hassanli, Kourosh
Abstract: A new design of a MEMS bionic vector hydrophone based on piezoelectric transduction has been proposed. The designed hydrophone has a higher sensitivity in comparison to its previous counterparts. Readout electronics includes embedded MOSFETs and external operational amplifiers. MOSFETs with piezoelectric gates are integrated to the beams and have been used as the strain to electrical current transducers. The drains of the MOSFETs have been connected to operational amplifiers that convert the transistor currents to the voltage and also amplify the output. The changes in the channel length and mobility are negligible and the transistor current is merely under the influence of the pressure induced charges on the piezoelectric surface which directly produce the vertical electric field. Designed hydrophone characterized with the sensitivity up to −146.2 ​dB (Ref. 1 ​V/μPa) for frequencies up to about 3 ​kHz. The results verify the possibility of utilizing the proposed design as an underwater acoustic sensor with a high sensitivity and a wide frequency range.